SYNTHESIS AND ADSORPTION STUDY OF PENICILLIN G USING AN ACRYLAMIDE-EGDMA MOLECULARLY IMPRINTED POLYMER - Puspita, Fitria; Sirumapea , Lasmaryna; Pratiwi, Fadila; Patmayuni, Dewi; Mualim, Ahmad Dzaky; Sirumapea, Lasmaryna (Lantanida Journal, 2026)
The widespread use of penicillin G demands highly selective analytical extraction methods for environmental and food residue monitoring. This study synthesized a Molecularly Imprinted Polymer (MIP) for the selective extraction of penicillin G via bulk polymerization, yielding 5.0 g of the MIP and 3.635 g of the non-imprinted polymer (NIP). Acrylamide was employed as the functional monomer, ethylene glycol dimethacrylate (EGDMA) as the cross-linker, and benzoyl peroxide (BPO) as the initiator. The template was successfully extracted using integrated Soxhlet and batch methods with a methanol-acetic acid (9:1, v/v) solvent system. FTIR spectroscopy confirmed the successful incorporation of monomeric functional groups, while Scanning Electron Microscopy (SEM) revealed a highly porous, irregular morphology in the MIP compared to the dense NIP. Equilibrium adsorption studies demonstrated that the MIP achieved an adsorption capacity of 6.40 mg/g, significantly outperforming the NIP (2.36 mg/g), yielding an imprinting factor (IF) of 2.71. Furthermore, the MIP exhibited competitive selectivity against ibuprofen as an analog molecule, achieving a selectivity coefficient (α) of 1.16. These results confirm that the synthesized acrylamide-based MIP provides high structural specificity, making it a highly robust sorbent for penicillin G analysis.